Pengaruh Pola Anyaman terhadap Sifat Mekanik Serat Kulit Pohon Melinjo untuk Pengembangan Produk Tas Noken - Ramandey , Johanis M; Suryadi , Suryadi; Liborang, Hans F; Dharsono, Wardhana Wahyu (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
This study aims to optimize the tensile strength of woven melinjo tree bark fibers in noken bag products as a superior regional product based on local wisdom. The research method used is an experimental approach with stages of literature study, material selection, determination of test parameters, creation of woven patterns, and tensile strength testing. Melinjo tree bark fibers were woven in three different patterns: 1-1, 1-2, and 2-2. The results showed that the weaving pattern significantly influences the mechanical properties of the fibers. The 2-2 weave pattern performed best in terms of tensile strength, with tensile stresses ranging from 24.8-25.2 N/mm². The 1-1 weave pattern had the highest elasticity and flexibility with 2.8% strain and 2.8% flexibility. The optimal weave pattern depends on the specific application and product requirements. These findings can serve as a basis for future development of melinjo tree bark fiber-based products, particularly noken bags as a superior regional product based on local wisdom.